Numerical analysis of core-scale methane hydrate dissociation dynamics and multiphase flow in porous media. (22nd October 2016) - Chen, Lin; Yamada, Hikaru; Kanda, Yuki; Lacaille, Guillaume; Shoji, Eita; Okajima, Junnosuke; Komiya, Atsuki; Maruyama, Shigenao
Abstract: Methane hydrate is one of the most promising future energy resources for humankind. In recent years, due to its vast existence in permafrost regions and deep ocean beds, increasing attention has been paid to the extraction, transportation and utilization of methane hydrate. The current study proposed core-scale numerical investigation models for the complex multiphase dissociation flows of methane hydrate inside porous media, which is a continuation and an extension of previous numerical investigations. The current numerical model focuses on the depressurization process and thermal boundary effects and discusses the parametric effects of the core-scale internal flows and controlling factors of the dissociation boundaries. The new findings with respect to the dissociation front movement and water–ice equilibrium effects during the dissociation process are also analyzed in this study. Ice formation and boundary heat conduction limitations are found to be critical for the smooth production of methane gas. Based on these results, trade off and production strategies for depressurization methods and thermal stimulation methods are also discussed in detail. It is hoped that this study will be useful for related core-scale analysis and possible engineering system designs. Highlights: New core-scale multi-phase flow and dissociation reaction model is set-up and validated. Inclined dissociation front movement for case under gravity are identified and compared. Boundary thermal effect is found critical for core-scale dissociation behaviors. Ice formation is identified and discussed with the general production strategies.